1991
DOI: 10.1139/t91-008
|View full text |Cite
|
Sign up to set email alerts
|

Field test of electroosmotic strengthening of soft sensitive clay

Abstract: A field test was undertaken to assess the effectiveness of electroosmosis in strengthening the soft sensitive (Leda) clay at the Gloucester test fill site. Specially designed copper electrodes were installed to prevent gas accumulation around the electrode and to allow pore water in the soil to flow out from the cathode without pumping. The variation of settlement, shear strength, and voltage distribution during treatment was measured, and tube samples were recovered before and after treatment for laboratory t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…Several successful field applications of electro-osmotic stabilization are quoted in literature (e.g. Fetzer 1967;Chappell and Burton 1975;Wade 1976;Lo et al 1991).…”
Section: Electro-osmotic Consolidationmentioning
confidence: 99%
See 2 more Smart Citations
“…Several successful field applications of electro-osmotic stabilization are quoted in literature (e.g. Fetzer 1967;Chappell and Burton 1975;Wade 1976;Lo et al 1991).…”
Section: Electro-osmotic Consolidationmentioning
confidence: 99%
“…Finally, after 2 more days of consolidation without applying current, the experiment was stopped. This sequence of testing was used to determine the test variables as polarity reversal (Lo et al 1991) had been reported to have a significant effect on electro-osmotic consolidation. However, polarity reversal did not show any effect on consolidation settlement.…”
Section: Departures In the Procedures In The Preliminary Test Series Imentioning
confidence: 99%
See 1 more Smart Citation
“…By applying an external electrical field to a soil mass, the pore water can be moved from anode to cathode along with the electromigration of cations, leading to the consolidation of the treated soil mass. Numerous laboratory experiments and field tests have been conducted to investigate the development of pore-water pressure and settlement during electroosmotic consolidation, and soil properties such as water content and shear strength after the treatment were measured to evaluate the effect of this technique (Bjerrum et al 1967;Esrig and Gemeinhardt 1967;Lo et al 1991;Lefebvre and Burnotte 2002;Cherepy and Wildenschild 2003;Glendinning et al 2007;Jeyakanthan et al 2011;Wu et al 2015a;Wu et al 2016). Since Casagrande (1949) first applied electroosmotic consolidation to improve the stability of fine soils, this technique has been used often in geotechnical engineering including during slope stabilization, soft ground improvement, tailing dewatering, sludge treatment, and so on (Glendinning et al 2005;Fourie et al 2007;Zhuang and Wang 2007;Jones et al 2008;Wu et al 2015b), and various methods have been proposed to improve its efficiency, such as intermittent current, electrode reversal, moving electrode, and a combination of surcharge and vacuum preloading (Shang 1998;Micic et al 2001;Yoshida et al 1999;Wu and Hu 2012;Zhan et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous studies and engineering practices [5,7,8], adding a salt solution, i.e., ECT, could enhance the electrical conductivity of the soil [23], increase the speed of dewatering, and promote the aggregation of soil particles caused by ion exchange [24 -26]. Many researchers have been performed on the ECT.…”
Section: Introductionmentioning
confidence: 99%